Cutaneous Nrf2‐Keap1 pathway modulation by environmental factors: The Dead Sea area as a test case. (15th December 2022) - Cohen, Dror; Portugal‐Cohen, Meital; Oron, Miriam; Frusic‐Zlotkin, Marina; Soroka, Yoram; Ma'or, Ze'evi; Amar, Dalit; Kohen, Ron
Abstract: The skin is constantly exposed to exogenous environmental stressors and has to cope with excessive oxidative stress and tissue damage. However, exposure to moderate environmental stressors may be beneficial for the cutaneous tissue and assist in protecting against oxidative damage via the enhanced activation of the nuclear factor erythroid 2‐related factor 2–Kelch‐like ECH‐associated protein 1 (Nrf2–Keap1) pathway. Such moderate stressors can be found in various locations around the globe. In this manuscript, we chose to focus on the Dead Sea (DS) area as a test case to study the effect of moderate stressors on the cutaneous tissue because of the unique combinations of moderate stressors in this area. The exceptional location of the DS at an altitude of −438 meters below sea level (the lowest place on earth) is responsible for its rare accumulation of moderate stressors such as high‐water salinity, high atmospheric pressure, and unique solar radiation. In this manuscript, we hypothesized that the unique solar radiation in the DS area generates moderate oxidative stress in the skin leading to the induction of intracellular electrophiles, which in turn can activate the protecting Nrf2‐Keap1 pathway. We showed that exposure of human skin organ culture from the same donor to solar radiation at the DS resulted in significant activation of the Nrf2‐Keap1 pathway, induction of phase II enzymes, and lower apoptotic activity compared to a nearby location at a higher altitude (Jerusalem +700 m). This remarkable effect of activating the Nrf2 protecting pathway and the importance and characteristics of the solar irradiation at the DS is discussed.